Eksplorasi Pengalaman Orang Tua Milenial Menggunakan Worksheet Tracing sebagai Alternatif Belajar Anak Usia 4–6 Tahun - Siti Nurpadila; Gilar Gandana; Anggi Maulana Rizqi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Millennial parents face increasing challenges in balancing children's digital exposure with developmentally appropriate learning activities. Previous studies have predominantly examined the effectiveness of tracing worksheets in improving children's fine motor skills, while little attention has been given to parents' lived experiences in integrating these media into everyday parenting practices. This study addresses this gap by exploring the subjective experiences of millennial parents using educational tracing worksheets as an alternative learning medium for children aged 4–6 years. Employing a descriptive phenomenological design, eight millennial parents were purposively selected and interviewed using semi-structured in-depth interviews. Data were analyzed through Moustakas' transcendental phenomenological procedures. Five essential themes emerged: tracing worksheets as a strategy to reduce gadget dependency, parental patience as both a prerequisite and an outcome of accompaniment, creative motivational strategies, strengthened parent-child emotional bonding, and tracing worksheets as a perceived writing-readiness medium. Ambivalent experiences, including concerns about visual fatigue and instructional dependency, were also identified. The novelty of this study lies in revealing tracing worksheets as a relational parenting medium that simultaneously negotiates digital parenting concerns, emotional interaction, and parental self-regulation, extending previous research that primarily emphasized children's developmental outcomes. The findings contribute theoretically to understanding digital parenting from a phenomenological perspective and practically suggest that tracing worksheets should be implemented through responsive parental guidance and integrated home-school collaboration to support balanced early childhood learning in the digital era